2020
DOI: 10.1177/1940161220925020
|View full text |Cite
|
Sign up to set email alerts
|

WhatsApp with Politics?!

Abstract: With an increasing number of people, especially adolescents, using more private online platforms, such as WhatsApp, for news, an important question for democracy is whether such platforms can facilitate learning about politics and current events. In this study, we examine adolescents’ affective (emotions, feelings), behavioral (actions and behavioral intentions), and cognitive (political knowledge) responses to interpersonal political discussion on WhatsApp. We conducted a preregistered field experiment at six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…La investigación en WhatsApp presenta dificultades por su carácter privado, pues supone un escenario en el que los contenidos son enviados de forma privada y no pueden auditarse por terceras personas sin que estas tengan permiso; es por ello que todavía no es un fenómeno muy estudiado. Experimentos exploratorios como el que realizan Vermeer et al (2020) con adolescentes arrojan algo de luz en el campo. Ellos analizan las implicaciones que la discusión política en grupos cerrados de WhatsApp puede tener para la democracia, y concluyen que las discusiones políticas en estos foros provocan sentimientos positivos en los participantes, pues al crearse redes sociales homogéneas estas discusiones promueven esperanza y entusiasmo.…”
Section: La Comunicación Política En Las Redes De Mensajería Instantáneaunclassified
“…La investigación en WhatsApp presenta dificultades por su carácter privado, pues supone un escenario en el que los contenidos son enviados de forma privada y no pueden auditarse por terceras personas sin que estas tengan permiso; es por ello que todavía no es un fenómeno muy estudiado. Experimentos exploratorios como el que realizan Vermeer et al (2020) con adolescentes arrojan algo de luz en el campo. Ellos analizan las implicaciones que la discusión política en grupos cerrados de WhatsApp puede tener para la democracia, y concluyen que las discusiones políticas en estos foros provocan sentimientos positivos en los participantes, pues al crearse redes sociales homogéneas estas discusiones promueven esperanza y entusiasmo.…”
Section: La Comunicación Política En Las Redes De Mensajería Instantáneaunclassified
“…Thus, the more exposure people have to social media content related to an issue, the more likely they are to discuss it within their social networks. This mechanism facilitates a thorough exchange of political views in both offline and online settings (Vermeer et al, 2021). Previous studies have demonstrated the possibility of transferring online expressions to networks originally built through offline ties like family, school, and the workplace (Wojcieszak, 2009).…”
Section: Social Media News Exposure and The Dual-orienting Processesmentioning
confidence: 99%
“…At the individual level, IMPs (e.g. WhatsApp, WeChat, Viber, Line and Skype) enable people to communicate with one another instantly by sending and receiving brief text-based messages, photographs, or emojis in real-time (Boyd and Ellison, 2008; Vermeer et al ., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%